‘Isolated in our own neighbourhood’: analysis on the proposal to regulate peer-to-peer accommodation services in Malaysia - Daud, Mahyuddin; Mat Isa, Norlaili (IIUM, 2021)
Peer-to-Peer Accommodation services (P2PA) are mushrooming worldwide due to the expansion of digital services and Internet access. Since P2PA services operate fully online, small establishments utilise disruptive technology and surpass traditional hoteliers by surprise. In the first part of this article, we examine the problems caused by P2PA for ‘playing on an uneven field’, avoiding necessary taxes, skipping regulatory and safety requirements, and causing loss of tranquillity to the neighbourhood. Due to these problems, a proposal was moved by the government to regulate P2PA in Malaysia via a self-regulatory guideline, as analysed in the second part of the article. However, due to its nonbinding status, the proposal will arguably lead to irregularities in regulatory mechanisms at the state level when enforced. P2PA hosts were asked to comply with regulatory requirements similar to hoteliers, but the platform providers have arguably avoided any P2PA related liability nor responsibility as they operate offshore. Applying qualitative research methods via content analysis and semi-structured interviews, the article concludes by proposing a legal framework to regulate the P2PA platform providers, including hosts and agents, which is deemed timely and necessary for Malaysia to safeguard the interests of both tourists and stakeholders.